Recent trends in the caesarean section rate in Ireland 1999 - 2006 - Aoife Brick; Richard Layte (The Economic and Social Research Institute (ESRI), 2009)
This paper explores levels and trends in the prevalence of caesarean section delivery in Ireland between 1999 and 2006. Over this period the caesarean section rate in Ireland increased by almost one quarter. Using data from the Irish National Perinatal Reporting System we examine the contribution of maternal, birth/infant and hospital characteristics on the rise in the caesarean section rate over the period. International evidence suggests that earlier gestational age of child, older maternal age at birth, higher socio-economic status of mother and birth within a private hospital all increase the risk of caesarean section. Controlling for changes in the prevalence of these and other risk factors between 1999 and 2006 only explains half of the increase in the caesarean section rate amongst singleton delivery first time mothers. This suggests that changes in physician behaviour over the period may well play a significant role.
Keywords: 330; Gesundheitsversorgung; Krankenhaus; Mütter; Geburtenrate; Medizin; Irland